Antiallodynic and antihyperalgesic effects of zerumbone on a mouse model of chronic constriction injury-induced neuropathic pain - Zulazmi, Nurul Atiqah; Gopalsamy, Banulata; Omar Farouk, Ahmad Akira; Sulaiman, Mohd Roslan; Bharatham, Hemabarathy; Perimal, Enoch Kumar (Elsevier, 2015)
Neuropathic pain is a chronic condition that is difficult to be treated. Current therapies available are either ineffective or non-specific thus requiring newer treatment approaches. In this study, we investigated the antiallodynic and antihyperalgesic effects of zerumbone, a bioactive sesquiterpene from Zingiber zerumbet in chronic constriction injury (CCI)-induced neuropathic pain animal model. Our findings showed that single and repeated dose of intra-peritoneal administration of zerumbone (5, 10, 50, 100 mg/kg) significantly attenuated the CCI-induced neuropathic pain when evaluated using the electronic von Frey anesthesiometer, cold plate, Randall-Selitto analgesiometer and the Hargreaves plantar test. Zerumbone significantly alleviated tactile and cold allodynia as well as mechanical and thermal hyperalgesia. Our findings are in comparison to the positive control drugs thatused gabapentin (20 mg/kgi.p.) and morphine (1 mg/kgi.p.). Together, these results showed that the systemic administration of zerumbone produced marked antiallodynic and antihyperalgesic effects in the CCI-induced neuropathic pain in mice and may serve as a potential lead compound for further analysis.